Antidiabetic potential of mangrove plants: a review. Issue 1 (2nd January 2016) - Das, Swagat Kumar; Samantaray, Dibyajyoti; Patra, Jayanta Kumar; Samanta, Luna; Thatoi, Hrudayanath
Abstract : Diabetes mellitus is a heterogeneous group of metabolic disorders characterized by persistent hyperglycaemia and becoming a serious threat to mankind health in all parts of the world. Production of reactive oxygen species and disturbed capacity of antioxidant defence have been reported for enhanced production of free radicals in diabetic subjects. As oxidative stress is found to be a central event in the development of diabetic complications, hence antioxidants may play an important role in the improvement of diabetes and its associated complications. Currently there has been an increased interest globally to identify antioxidant compounds that are pharmacologically potent and have low or no side effects. Phytochemicals and metabolites from mangrove plants are reported to exhibit strong antioxidant properties in terms of both enzymatic and non-enzymatic activities. Recent researches have also revealed that a number of mangrove plants have shown antidiabetic activities attributed to their unique metabolites such as flavonoids, triterpenoids, limonoids and polysaccharides. Thus, mangrove plants can be of great use in tackling diabetic and its associated oxidative stress mediated complications. The present review highlights a relation between oxidative stress and diabetes and the role of mangrove plants in alleviating diabetes, in general, and oxidative stress mediated diabetic complications, in particular.